Heredia, Juanita. Mapping South American Latina/o Literature in the United States: Interviews with Contemporary Writers, Palgrave MacMillan, 2019. - Manuela Borzone (Studies in 20th & 21st Century Literature, 2022)
Review of Juanita Heredia. Mapping South American Latina/o Literature in the United States: Interviews with Contemporary Writers, Palgrave MacMillan, 2019. vii + 238 pp.
Keywords: South America; Latina/o Writers; multiethnic literature; hemispheric studies